โลกาภิวัตน์วัฒนธรรม : สื่อกับท้องถิ่นนิยมในวรรณกรรมไทยร่วมสมัย - ธนิกาญจน์ จินาพันธ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To analyze cultural globalization concept and media role on globalization flow which affects localism in Thai contemporary literature composed during 1997-2007. The study shows that the development of significant concepts of cultural globalization in Thai contemporary literature reveals authors viewpoint in two categorized periods. In the first period (1997-2005), cultural globalization is the domination by western culture. Its appearance is seen as an evil, invading local areas and was blamed for the fall of local’s identity. The portrayal of the local, therefore, unveils the resistance and repulsion against globalization flow. In the second period (2006-2007), however, cultural globalization represents the diversity of cultures and the shifting of power. In this period, the image of the local shows how it repels, yet conciliates with globalization in order to co-exist. Such condition is conducted by teasing and challenging globalization, weakening the power of cultural globalization in its flow, meanwhile generating the construction of local culture. The image of the local in Thai contemporary literature unveils the role of media and globalization flow that affects it. Media plays a significant role in creating the imagined world by reporting information and by turning localism into a way of capitalism and consumerism. In cultural globalization context, ‚localism is the concept chosen by authors to resist globalization flow, yet meanwhile questioning the concept. In the world where diverse cultures flow about in a society, to live with sole belief in localism and reject globalization would eventually leads to the end of the local.